RANCANG BANGUN ALAT PENGHASIL AIR ALKALI SEBAGAI PENGOBATAN ALTERNATIF BERBASIS MIKROKONTROLLER - H. Ary Setyadi - STMIK AUB Surakarta; Priyanggara Siddhi Permana - STMIK AUB Surakarta (SPEED - Sentra Penelitian Engineering dan Edukasi, 2018)
ABSTRACT - Health is important for every society due to perform daily activities necessary condition of a healthy body in order to do something anything can running optimally. One way to get a healthy body condition is to keep eat and drink. Alkaline water is the treated water thus achieving a measure of acidity in the pH of 8 to 9 or more than 9. For information, the pH of the water safe to drink should range between 8.5 to 11.5. high pH in drinking water can make the blood pH becomes too alkali or alkaline, which is believed to make the body more healthy. Installation tools Tools To Make Water As An Alternative For Health Based Mikrokontroller ATmega16 then started from the pH sensor output is connected to the ATmega1,  6 Microcontroller input, then the output is connected LCD, Alarm and AC voltage output. The main working principle pH meter is located on the sensor probe in the form of glass electrode (glass electrode) by measuring the amount of H3O + ions in solution. The tip of the glass electrode is 0.1 mm thick layer of glass which are round (bulb). Bulb glass cylinder is paired with a non-conductor or elongated plastic, which is subsequently filled with a solution of HCl (0.1 mol / dm3). In a solution of HCl, submerged a length of wire electrode made from silver on its surface formed an equilibrium compounds AgCl. The constant amount of HCl solution in this system makes the electrode Ag / AgCl potential value stable. For level detection sensor is in use the sensitivity level is still low, expected in its development could be noticed again in the use of sensors as the main component in the manufacture of this instrument.Keywords: Health, ATMEGA16, pH Sensor, Alkaline Water ABSTRAK – Salah satu cara mendapatkan kondisi badan yang sehat adalah dengan cara menjaga pola makan dan minum. Air alkali adalah air yang diolah sehingga mencapai keasaman dalam ukuran pH 8 hingga 9 atau lebih dari 9. Sebagai informasi, pH air yang sehat untuk diminum harus berkisar antara 8,5 – 11,5. pH tinggi pada air minum dapat membuat pH darah juga menjadi alkali atau basa, yang diyakini bisa membuat tubuh lebih sehat. Pemasangan alat Alat Untuk Menghasilkan Air Sebagai Alternatif Bagi Kesehatan Berbasis Mikrokontoller ATMega16 dimulai dari sensor pH kemudian keluarannya dihubungkan pada masukan Mikrokontroller ATMega16, kemudian keluaran dihubungkan  LCD, Alarm dan keluaran tegangan AC. Prinsip kerja utama pH meter adalah terletak pada sensor probe berupa elektrode kaca (glass electrode) dengan jalan mengukur jumlah ion H3O+ di dalam larutan. Ujung elektrode kaca adalah lapisan kaca setebal 0,1 mm yang berbentuk bulat (bulb). Bulb ini dipasangkan dengan silinder kaca non-konduktor atau plastik memanjang, yang selanjutnya diisi dengan larutan HCl (0,1 mol/dm3). Di dalam larutan HCl, terendam sebuah kawat elektrode panjang berbahan perak yang pada permukaannya terbentuk senyawa setimbang AgCl. Konstannya jumlah larutan HCl pada sistem ini membuat elektrode Ag/AgCl memiliki nilai potensial stabil. Untuk tingkat pendeteksi sensor yang di pakai tingkat sensifitasnya masih rendah, diharapkan dalam pengembanganya bisa lebih di perhatikan lagi dalam pengunaan sensor sebagai komponen utama dalam pembuatan alat ini.Kata Kunci        : Kesehatan, ATMEGA16, Sensor pH, Air Alkali